2007
DOI: 10.1093/annonc/mdm199
|View full text |Cite
|
Sign up to set email alerts
|

Preferences regarding end-of-life cancer care and associations with good-death concepts: a population-based survey in Japan

Abstract: End-of-life care preferences were associated with good-death concepts. It would be useful for health-care workers to discuss patients' good-death concepts to support subsequent treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 35 publications
7
92
0
1
Order By: Relevance
“…Among them, multiple empirical studies have identified knowledge, beliefs, or concerns about opioids, palliative care, and homecare in the general population and cancer patients as potential barriers for quality palliative care [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Many surveys have shown that incorrect knowledge about cancer pain and opioids could interfere with optimal pain management, especially an unrealistic fear of addiction and life-shortening [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, multiple empirical studies have identified knowledge, beliefs, or concerns about opioids, palliative care, and homecare in the general population and cancer patients as potential barriers for quality palliative care [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Many surveys have shown that incorrect knowledge about cancer pain and opioids could interfere with optimal pain management, especially an unrealistic fear of addiction and life-shortening [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Negative beliefs about palliative care were also one of the significant determinants of the potential underuse of specialized palliative care services [8][9][10][11][12]. Moreover, many patients have concerns and difficulties about homecare, such as the burden on the family, concerns about sudden changes in physical conditions, and the unavailability of physicians visiting their home, and these could influence patients' decisions regarding whether or not to receive homecare [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care units must shift focus more on palliation from care for imminently dying patients [13] and caring for terminally ill cancer patients at home for as long as possible. The hypothesis that a prolonged stay at home would contribute to quality of dying is supported by evidence that the general population's preferences for places to live at the end-of-life and to die are different [6]. Improvements in outpatient care may also contribute to removing the negative image of palliative care units as the final residence for these patients [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of Japanese individuals prefer home care when diagnosed with a terminal illness (1), but census data indicate that only 7% of the Japanese cancer patients died in their own homes (2). This discordance is probably due to the complexities of decision-making for end-of-life care.…”
Section: Introductionmentioning
confidence: 99%